Ibn Taymiyah's Political Thoughts on Leadership and Its Relevance to the Criteria for Candidates for People's Leaders in Indonesia - Husna Hisaba Kholid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The still high level of corruption among people's leaders in Indonesia shows the importance of reviewing the criteria for candidates for people's leaders in this country. In reality, the candidate criteria that have been set so far in the elections have not provided a positive assessment of the leaders who have been elected so far. On this basis, new views are needed to offer criteria for more ideal leaders in the future. Regarding this leadership problem, Ibn Taymiyyah, a great Islamic figure, gave the idea of ​​the concept of an ideal leader in a country. Therefore, this paper aims to intensively reveal Ibn Taymiyyah's political thinking on leadership issues. Next, the author analyzes his thoughts on how relevant they are to the criteria for potential leaders of the people in Indonesia. This research is library research and the data sources used consist of primary data sources from Ibn Taimiyyah's works related to the concept of leadership and secondary data sources, namely books, which are relevant to this research to strengthen arguments and to complement the data from research result. The data analysis technique used by the author in this research is content analysis. The results that the author got from this study are as follows. First, Ibn Taymiyyah paid great attention to the religious aspects of a leader in his political thinking. Second, for Ibnu Taimiyyah, a leader must have at least two criteria which he calls quwwah and amanah. Third, this view is worth reading and reviewing to provide an alternative view for determining the criteria for a more ideal leader candidate in Indonesia. Based on these findings, the author hopes that there will be further studies to determine practical indicators in Ibnu Taymiyyah's ideas so that these ideas are easier to implement in political conditions in Indonesia